(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Water dams are typical structures which require cyclic and in some cases, permanent control of their conditions. Most of the Polish damming structures are more than fifty years old and funds assigned for their renovation and effective conservation are being continuously reduced. Therefore, it is vital to improve the control of those structures.Cyclic geodetic measurements of movements are obligatory elements of control measurement schedule and are important for evaluation of damming structures security. Complex modernisation of geodetic network for movement examination consists of many actions, which goals are:- Reactivating devastated network structure,- Modernisation of geodetic process of structures movements determination (concerning steps: measurements and data elaborating),- Enhancing the accuracy of geodetic measurements,Increasing a credibility of the movement measurements results.